Impact Tax Policy on CPO Exports - Syadullah, Makmun (Badan kebijakan Fiskal, 2014)
CPO is a strategic commodity in the global market, so that the condition and CPO prices in the domestic market is strongly influenced by the global market. This study aims to analyze several factors that affect CPO export, namely CPO price in the international market, the exchange rate rupiah against the US dollar and tax policy as stated in the PMK No. 128 / PMK.011 / 2011. Based on this research, in the period 2005-2013 Indonesia's CPO exports was influenced by the CPO price in the international market, the exchange rate rupiah against the US dollar and tax policy in 2011. Overall the model is able to explain that variation changes CPO exports in the period 2005-2013 by 73,73%t are influenced by the three variables used in this model, while the rest is influenced by other variables that are not included in this study observations. while the rest is influenced by other variables that are not included in this study observations.